Positive plate, and electrochemical device and electronic device comprising same
By controlling the molar ratio of manganese element and phosphorus element on the surface of the positive electrode active material layer of the positive electrode sheet of the lithium-ion battery and adding phosphorus compounds, the problem of specific capacity decay of lithium-ion battery at high temperatures is solved, and the high-temperature storage and cycling performance is significantly improved.
Patent Information
- Application Number
- CN202510098127.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2021-02-03
- Publication Date
- 2025-04-18
AI Technical Summary
Existing lithium-ion batteries have severely decayed specific capacity in high temperature environments, resulting in the impact of stability and service life.
The molar ratio of manganese element and phosphorus element is controlled to be from 70:1 to 450:1 on the surface of the positive electrode active material layer of the positive electrode sheet, and the phosphorus compound is contained in the positive electrode active material layer, thereby improving the interface stability.
It significantly improves the high-temperature storage and high-temperature cycling performance of electrochemical devices and extends the service life of electrochemical devices.
Smart Images

Figure CN119852414A_ABST
Abstract
Description
[0001] This application is a divisional application of a patent application with an application date of February 3, 2021, application number 202180003229.9, and invention name “Positive electrode sheet and electrochemical device and electronic device containing the positive electrode sheet”. Technical Field
[0002] The present application relates to the field of energy storage technology, and in particular to a positive electrode sheet and an electrochemical device and an electronic device comprising the positive electrode sheet. Background Art
[0003] With the popularity of consumer electronic products such as laptops, mobile phones, tablets, mobile power supplies and drones, the requirements for electrochemical devices therein (such as lithium-ion batteries) are becoming more and more stringent. For example, lithium-ion batteries are not only required to have a higher specific capacity, but also to be stable under high temperature environments. However, the current lithium-ion batteries have a serious capacity decay at high temperatures. This is because high temperatures promote the occurrence of side reactions inside lithium-ion batteries, resulting in the destruction of the structure of electrode active materials, affecting the stability and service life of lithium-ion batteries. Therefore, there is an urgent need for a lithium-ion battery that has a long service life even at high temperatures. Summary of the invention
[0004] The purpose of the present application is to provide a positive electrode sheet and an electrochemical device and an electronic device comprising the positive electrode sheet, so as to improve the stability of the electrochemical device in a high temperature environment.
[0005] In some embodiments, the present application provides a positive electrode sheet, which includes a positive electrode active material layer, and the element content on the surface of the positive electrode active material layer satisfies: the molar ratio of manganese element to phosphorus element ranges from 70: 1 to 450: 1. In some embodiments, the molar ratio of manganese element to phosphorus element ranges from 70: 1 to 200: 1.
[0006] In some embodiments, the thickness of the positive electrode active material layer is H, and the molar ratio of phosphorus to manganese on the surface of the positive electrode active material layer is P. o The molar ratio of phosphorus to manganese in the positive electrode active material layer at a depth of H / 4 to H / 3 from the surface of the positive electrode active material layer is P i , P o / P i In some embodiments, P o / P i 1 to 1.38.
[0007] In some embodiments, in the XRD spectrum of the surface of the positive electrode active material layer, I A Indicates the peak intensity of the characteristic peak in the range of 20° to 21°, I BIndicates the peak intensity of the characteristic peak in the range of 18° to 18.6°, 0.12 ≤ I A / I B ≤ 0.2.
[0008] In some embodiments, the positive electrode active material layer includes a positive electrode active material and a phosphorus-containing compound. The average particle size of the positive electrode active material is D1, and the average particle size of the phosphorus-containing compound is D2, 0.33 ≤ D1 / D2 ≤ 100. In some embodiments, 2 ≤ D1 / D2 ≤ 100.
[0009] In some embodiments, the surface of the positive electrode active material has the phosphorus-containing compound, and the thickness h of the phosphorus-containing compound is 10 nm to 30 nm.
[0010] In some embodiments, the average particle size D1 of the positive electrode active material is 2 μm to 30 μm, and the average particle size D2 of the phosphorus-containing compound is 0.1 μm to 30 μm. In some embodiments, D1 is 10 μm to 25 μm, and D2 is 0.1 μm to 5 μm.
[0011] In some embodiments, the phosphorus-containing compound includes A x PO y , where A includes at least one of Li, Na, K, Mg, Ca, Y, Sr, Ba, Zn, Al, or Si, 1 ≤ x ≤ 4, 3 ≤ y ≤ 4.
[0012] In some embodiments, the positive electrode active material includes at least one of compound a) or compound b): Compound a) Li x1 Mn 2-y1 Z y1 O4, where Z includes at least one of Mg, Al, B, Cr, Ni, Co, Zn, Cu, Zr, Ti, or V, 0.8 ≤ x1 ≤ 1.2, 0 ≤ y1 ≤ 0.1; Compound b) Li x2 Ni y2 Co z Mn k M q O b-a T a , where M includes at least one of B, Mg, Al, Si, P, S, Ti, Cr, Fe, Co, Ni, Cu, Zn, Ga, Y, Zr, Mo, Ag, W, In, Sn, Pb, Sb, or Ce; T is a halogen, and x2, y2, z, k, q, a, and b respectively satisfy: 0.2 ≤ x2 ≤ 1.2, 0 ≤ y2 ≤ 1, 0 ≤ z ≤ 1, 0 < k ≤ 1, 0 ≤ q ≤ 1, 1 < b ≤ 2, and 0 ≤ a ≤ 1.
[0013] In some embodiments, the mass ratio of the positive electrode active material to the phosphorus-containing compound is 95-97:0.5-3.
[0014] In some embodiments, the present application also provides an electrochemical device, which includes the positive electrode sheet described above in the present application.
[0015] In some embodiments, the present application further provides an electronic device, which includes the electrochemical device described above in the present application.
[0016] The technical solution of the present application has at least the following beneficial effects: when the molar ratio of manganese element to phosphorus element on the surface of the positive electrode active material layer satisfies the range of 70:1 to 450:1, it can improve the interfacial stability of the manganese-containing positive electrode sheet in the electrolyte and significantly improve the high-temperature storage and high-temperature cycle performance of the electrochemical device. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1a Raman spectra of the positive electrode sheet in a fresh state, after formation, and after storage, respectively, used in the lithium-ion battery of Example 1; Figure 1b The Raman spectra of the positive electrode sheet used in the lithium-ion battery of Comparative Example 1 in the fresh state, after formation and after storage;
[0018] Figure 2 In order to disassemble the lithium-ion battery after formation, the P spectrum of the EDX-Mapping of the positive electrode active material layer surface of the positive electrode sheet measured by the SEM-EDX method; wherein, Figure 2 The control group in the figure corresponds to the positive electrode of the corresponding ratio 1. Figure 2 The experimental group in corresponds to the positive electrode sheet of Example 1;
[0019] Figure 3 The lithium-ion batteries of Example 1 and Comparative Example 1 are disassembled after formation, and the XRD patterns of the surfaces of the positive electrode active material layers of the positive electrode sheets. DETAILED DESCRIPTION
[0020] It will be understood that the disclosed embodiments are merely examples of the present application, which can be implemented in various forms, and therefore, the specific details disclosed herein should not be interpreted as limiting, but merely as the basis for the claims and as a representative basis for teaching one of ordinary skill in the art to implement the present application in various ways.
[0021] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unclearly recorded range: and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.
[0022] In this application, the average particle size refers to the observation of the material powder by SEM scanning electron microscope, and then, using image analysis software, 10 material particles are randomly selected from the SEM photo, and the area of each of these material particles is calculated. Then, assuming that the material particles are spherical, the particle size R (diameter) of each is calculated by the following formula: R = 2 × (S / π) 1 / 2 ; Wherein, S is the area of the material particles; 10 SEM images are processed to obtain the particle size R of the material particles, and the particle sizes of 100 (10×10) material particles are arithmetic averaged to obtain the average particle size of the material particles.
[0023] [Positive electrode]
[0024] A first aspect of the embodiments of the present application provides a positive electrode sheet.
[0025] In some embodiments, the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer. The positive electrode active material layer is disposed on the surface of the positive electrode current collector. In some embodiments, the positive electrode current collector is a metal, such as but not limited to aluminum foil. In some embodiments, the positive electrode active material layer includes manganese and phosphorus.
[0026] When the positive electrode active material layer contains manganese, at least a portion of the manganese is usually in the form of Mn 3+ In the form of, for example, lithium manganese oxide materials, nickel cobalt lithium manganese oxide materials. Since the electrolyte of the electrochemical device usually contains trace amounts of water, water and lithium salt LiPF6 in the electrolyte react easily to form HF. Under the action of HF, Mn 3+ Prone to disproportionation reaction to generate Mn 4+ and Mn 2+ On the one hand, Mn 2+ It is easy to dissolve, especially at high temperature, which further accelerates the dissolution. The dissolution process causes the particle structure of the positive electrode material to be destroyed. On the other hand, Mn dissolved in the electrolyte during charging 2+Diffused from the positive electrode to the negative electrode, manganese is deposited on the surface of the negative electrode in the form of metal, destroying the SEI film on the surface of the negative electrode. The positive active material layer of the present application contains phosphorus, which can complex HF, thereby significantly reducing the content of HF in the electrolyte and improving the stability of the electrochemical device; at the same time, the present application sets the element content on the surface of the positive active material layer to meet the molar ratio of manganese to phosphorus in the range of 70:1 to 450:1. In some embodiments, the molar ratio of manganese to phosphorus is in the range of 70:1 to 200:1. The surface of the positive active material layer in the present application refers to the surface of the positive active material layer away from the current collector. By controlling the amount of phosphorus on the surface of the positive active material layer to meet a certain range, the HF near the surface of the positive active material layer can be fully complexed to avoid the dissolution of manganese in the electrolyte, which can improve the stability of the electrochemical device under high temperature conditions and extend the service life of the electrochemical device. When the content of phosphorus is higher than this range, the impedance of the surface of the positive active material layer is too large; when the content of phosphorus is lower than this range, the improvement effect of high temperature performance is not good.
[0027] In the embodiments of the present application, the manganese and phosphorus content on the surface of the positive electrode active material layer can be measured by any method known in the art that can measure the manganese and phosphorus content. In some embodiments, the present application can be measured by the following SEM-EDX test method: first, select an area of 200μm×200μm in the SEM-EDX image of the surface of the positive electrode active material layer, and test the number of P atoms N1 in the entire area; then test the number of Mn atoms N2 within the area; the molar ratio of Mn / P in the area is W1=N2 / N1.
[0028] In the embodiments of the present application, there is no particular limitation on the preparation method of the positive electrode active material layer, and a preparation method known to those skilled in the art can be used. For example, the positive electrode active material containing the Mn element and the phosphorus-containing compound can be mixed in the positive electrode slurry, and then the positive electrode slurry can be coated on the positive electrode current collector to prepare the positive electrode active material layer. Among them, when preparing a positive electrode active material layer having different concentrations of phosphorus-containing compounds in the thickness direction, the differences in deposition rate and filling properties caused by the differences in density and particle size between the phosphorus-containing compound and the positive electrode active material can be utilized, and the drying temperature and rate can be controlled to achieve different concentrations of phosphorus-containing compounds in the thickness direction of the positive electrode active material layer. In addition, a positive electrode active material layer having different concentrations of phosphorus-containing compounds in the thickness direction can also be prepared by layered coating. Layered coating refers to coating the positive electrode slurry layer by layer on the positive electrode current collector. The ratio of the positive electrode active material to the phosphorus-containing compound in the positive electrode slurry coated in each layer can be the same or different. By setting the ratio of the positive electrode active material to the phosphorus-containing compound in the positive electrode slurry coated in each layer to be different, the difference in the content of the phosphorus-containing compound in the thickness direction of the positive electrode active material layer can be controlled.
[0029] In some embodiments, the thickness of the positive electrode active material layer is H, and the molar ratio of phosphorus to manganese on the surface of the positive electrode active material layer is P. o The molar ratio of phosphorus to manganese in the positive electrode active material layer at a depth of H / 4 to H / 3 from the surface of the positive electrode active material layer is P i , P o / P i is 0.5 to 2. While ensuring that the amount of phosphorus on the surface of the positive electrode active material layer meets a certain range, ensuring that a considerable amount of phosphorus also exists inside the positive electrode active material layer near the surface can reduce the side reactions inside the positive electrode active material layer and further improve the high temperature stability of the electrochemical device. In some embodiments, P o / P i 1 to 1.38.
[0030] In the embodiment of the present application, the molar ratio of phosphorus to manganese on the surface of the positive electrode active material layer is P o , and the molar ratio of phosphorus and manganese in the region of depth H / 4 to H / 3 from the surface of the positive electrode active material layer is P i , any method known in the art that can determine the content of phosphorus and manganese can be used for determination. In some embodiments, the present application can be determined by the following SEM-EDX test method: first, an area of 200 μm×200 μm is selected from the surface SEM-EDX image of the positive electrode active material layer, and the molar ratio P of phosphorus and manganese in the entire area is tested. o Then, an area of 200 μm×200 μm was selected from the SEM-EDX image of the H / 4 to H / 3 depth region from the surface of the positive electrode active material layer, and the molar ratio P of phosphorus and manganese in the entire area was tested. i ; The ratio of the two is P o / P i .
[0031] In the embodiment of the present application, when a positive electrode active material layer having different concentrations of phosphorus-containing compounds in the thickness direction is prepared by layered coating, a positive electrode slurry having a lower phosphorus-containing compound ratio is first coated, and then a positive electrode slurry having a higher phosphorus-containing compound ratio is coated, so that P o / P i The value is greater than 1 and less than or equal to 1.38.
[0032] In some embodiments, the positive electrode active material layer includes a positive electrode active material. In some embodiments, the positive electrode active material includes at least one of compound a) or compound b): compound a) Li x1 Mn 2-y1 Z y1O4, where Z includes at least one of Mg, Al, B, Cr, Ni, Co, Zn, Cu, Zr, Ti, or V, 0.8 ≤ x1 ≤ 1.2, 0 ≤ y1 ≤ 0.1; compound b) Li x2 Ni y2 Co z Mn k M q O b-a T a , where M includes at least one of B, Mg, Al, Si, P, S, Ti, Cr, Fe, Co, Ni, Cu, Zn, Ga, Y, Zr, Mo, Ag, W, In, Sn, Pb, Sb, or Ce; T is a halogen, and x2, y2, z, k, q, a, and b respectively satisfy: 0.2 ≤ x2 ≤ 1.2, 0 ≤ y2 ≤ 1, 0 ≤ z ≤ 1, 0 < k ≤ 1, 0 ≤ q ≤ 1, 1 < b ≤ 2, and 0 ≤ a ≤ 1.
[0033] The manganese element is added to the positive electrode active material layer in the form of lithium manganate - based positive electrode active material and / or ternary positive electrode active material. Lithium manganate - based materials (Li x1 Mn 2-y1 Z y1 O4) have a relatively high theoretical specific capacity as the positive electrode active material of a lithium - ion battery, high safety performance, an average potential relative to the lithium electrode of about 3.9 V, and a relatively high commercial cost - performance. However, lithium manganate - based materials have a serious specific capacity decay during charge - discharge processes, especially at high temperatures (above 60 °C). In this application, by better complexing HF in the electrolyte, it is possible to avoid the disproportionation reaction of Mn 3+ in lithium manganate - based materials, avoid the formation of Mn 2+ , thereby avoiding the destruction of the structure of lithium manganate. At the same time, it is possible to avoid the Jahn - Teller effect during the charge - discharge process of spinel lithium manganate, avoid crystal distortion when the manganese valence is lower than +3.5, and thus avoid the lattice distortion caused by the transformation from the cubic phase to the tetragonal phase, effectively solving the problem of specific capacity decay of lithium manganate - based materials at high temperatures.
[0034] The phosphorus element is added to the positive electrode active material layer in the form of a phosphorus - containing compound. In some embodiments, the positive electrode active material layer includes a phosphorus - containing compound, and the phosphorus - containing compound includes A x PO y , where A includes at least one of Li, Na, K, Mg, Ca, Y, Sr, Ba, Zn, Al, or Si, 1 ≤ x ≤ 4, 3 ≤ y ≤ 4.
[0035] In some embodiments, the average particle size of the positive electrode active material is D1, the average particle size of the phosphorus-containing compound is D2, and 0.33≤D1 / D2≤100. When the positive electrode active material and the phosphorus-containing compound meet the above conditions, the phosphorus-containing compound can be evenly dispersed in the positive electrode active material layer. When D1 / D2<0.33, the particle size of the phosphorus-containing compound is relatively large, which makes it difficult to evenly distribute the phosphorus-containing compound in the positive electrode active material layer, and the stability is poor due to the lack of effective protection of the phosphorus-containing compound in some parts; and when D1 / D2>100, the particle size of the phosphorus-containing compound is relatively small, and more will be deposited in the lower layer of the positive electrode active material layer during the coating process, filling the pores between the positive electrode active materials, resulting in the lack of effective protection of the phosphorus-containing compound on the surface of the positive electrode active material layer, and the small-sized phosphorus-containing compound is easy to agglomerate, and it is also difficult to disperse evenly.
[0036] In some embodiments, the surface of the positive electrode active material has the phosphorus-containing compound, and the thickness h of the phosphorus-containing compound is 10nm to 30nm. When the positive electrode active material and the phosphorus-containing compound meet the above conditions, a solid solution interface is formed between the phosphorus-containing compound and the positive electrode active material, which can effectively protect the surface of the positive electrode active material while avoiding the problem of increased impedance caused by excessive thickness. During preparation, the positive electrode active material precursor is mixed evenly with the lithium source and the phosphorus-containing compound by high-speed mechanical mixing, and sintering can obtain a positive electrode active material with a surface coated with a phosphorus-containing compound.
[0037] In some embodiments, the average particle size D1 of the positive electrode active material is 2 μm to 30 μm. In some embodiments, the average particle size D2 of the phosphorus-containing compound is 0.1 μm to 30 μm.
[0038] In some embodiments, the average particle size D1 of the positive electrode active material is 10 μm to 25 μm. In some embodiments, the average particle size D2 of the phosphorus-containing compound is 0.1 μm to 5 μm.
[0039] The mass ratio of the positive electrode active material to the phosphorus-containing compound affects the distribution of manganese and phosphorus in the positive electrode active material layer, and when the mass ratio of the positive electrode active material to the phosphorus-containing compound meets a certain range, it is beneficial to adjust the distribution of phosphorus in the positive electrode active material layer, promote the complexation of P and HF, and further improve the high temperature stability of the electrochemical device. In some embodiments, the mass ratio of the positive electrode active material to the phosphorus-containing compound is 95-97:0.5-3.
[0040] In some embodiments, in the XRD spectrum of the surface of the positive electrode active material layer, I A Indicates the peak intensity of the characteristic peak in the range of 20° to 21°, I B Indicates the peak intensity of the characteristic peak in the range of 18° to 18.6°, 0.12≤I A / IB ≤0.2. Among them, the peak intensity of the characteristic peak in the range of 20° to 21° corresponds to the content of phosphorus-containing compounds in the positive electrode active material layer, and the peak intensity of the characteristic peak in the range of 18° to 18.6° corresponds to the content of lithium manganate in the positive electrode active material layer. The positive electrode active material layer with such a characteristic peak intensity ratio indicates that there is a sufficient amount of phosphorus-containing compounds on the surface of the positive electrode active material layer, which can reduce the damage of HF to the positive electrode active material.
[0041] In some embodiments, the positive electrode active material layer further includes a positive electrode binder. The positive electrode binder is used to improve the bonding performance between the positive electrode active material particles and between the positive electrode active material particles and the positive electrode current collector. The positive electrode binder is a binder known in the art that can be used as a positive electrode active material layer. In some embodiments, the positive electrode binder includes polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin, and at least one of nylon.
[0042] In some embodiments, the positive electrode active material layer further includes a positive electrode conductive agent. The positive electrode conductive agent is used to improve the conductivity of the positive electrode sheet. The positive electrode conductive agent is a conductive agent known in the art that can be used as a positive electrode active material layer. In some embodiments, the positive electrode conductive agent includes at least one of graphite, conductive carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, graphene, metal powder, and metal fiber. In some embodiments, the metal in the metal powder and the metal fiber includes at least one of copper, nickel, aluminum, and silver.
[0043] The present application has no particular limitation on the mixing ratio of the positive electrode active material, the positive electrode binder, and the positive electrode conductive agent in the positive electrode active material layer, and the mixing ratio can be controlled according to the desired performance of the electrochemical device.
[0044] [Electrochemical device]
[0045] The second aspect of the embodiment of the present application provides an electrochemical device. The electrochemical device of the present application is, for example, a primary battery or a secondary battery. The secondary battery is, for example, a lithium secondary battery, which includes but is not limited to a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery. In some embodiments, the electrochemical device includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte, and the positive electrode sheet is the positive electrode sheet of the first aspect of the present application.
[0046] In some embodiments, the electrochemical device is discharged to a 25% state of charge and then stored at 80°C for 1 day. After disassembly, the positive electrode sheet is washed with dimethyl carbonate solvent and dried at 85°C for 12 hours. The Raman spectra of the positive electrode sheet at 258-846 cm -1 There are two peaks in the wavelength range, and the ratio of the strongest peak to the second strongest peak is 1.6 to 2.0, indicating that the surface lithium manganese oxide still has the initial crystal structure and is well protected.
[0047] Negative plate
[0048] The negative electrode sheet is a negative electrode sheet known in the art that can be used in an electrochemical device. In some embodiments, the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer. The negative electrode active material layer is disposed on the surface of the negative electrode current collector.
[0049] In some embodiments, the negative electrode current collector is a metal, such as but not limited to copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or a combination thereof.
[0050] In some embodiments, the negative electrode active material layer includes a negative electrode active material. The negative electrode active material can be selected from various conventionally known materials that can be used as electrochemical devices and can embed and de-embed active ions, or conventionally known materials that can dope and de-dope active ions, which are known in the art. In some embodiments, the negative electrode active material includes at least one of a carbon material, a silicon material, lithium metal, a lithium metal alloy, and a transition metal oxide. In some embodiments, the carbon material includes at least one of natural graphite, artificial graphite, soft carbon, hard carbon, a mesophase pitch carbonization product, and fired coke.
[0051] In some embodiments, the negative electrode active material layer further includes a negative electrode binder. The negative electrode binder is used to improve the bonding performance between the negative electrode active material particles and between the negative electrode active material particles and the negative electrode current collector. The negative electrode binder is a binder known in the art that can be used as a negative electrode active material layer. In some embodiments, the negative electrode binder includes polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin, and at least one of nylon.
[0052] In some embodiments, the negative electrode active material layer further includes a negative electrode conductive agent. The negative electrode conductive agent is used to improve the conductivity of the negative electrode sheet. The negative electrode conductive agent is a conductive agent known in the art that can be used as a negative electrode active material layer. In some embodiments, the negative electrode conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, graphene, metal powder, metal fiber and polyphenylene derivatives. In some embodiments, the metal in the metal powder and metal fiber includes at least one of copper, nickel, aluminum and silver.
[0053] In some embodiments, the method for preparing the negative electrode sheet is a method for preparing the negative electrode sheet that can be used for an electrochemical device that is well known in the art. In some embodiments, in the preparation of the negative electrode slurry, a solvent, a negative electrode active material and a negative electrode binder are usually added, and a negative electrode conductive agent and a thickener are added as needed to form a negative electrode slurry. The solvent is evaporated and removed during the drying process. The solvent is a solvent that can be used as a negative electrode active material layer that is well known in the art, and the solvent is for example, but not limited to, water and N-methylpyrrolidone. The thickener is a thickener that can be used as a negative electrode active material layer that is well known in the art, and the thickener is for example, but not limited to, sodium carboxymethyl cellulose. The present application has no particular restrictions on the mixing ratio of the negative electrode active material, the negative electrode binder, the negative electrode conductive agent, and the thickener in the negative electrode active material layer, and the mixing ratio can be controlled according to the desired electrochemical device performance.
[0054] Electrolyte
[0055] The electrolyte is an electrolyte known in the art that can be used in electrochemical devices. In some embodiments, the electrolyte includes an organic solvent, an electrolyte salt, and an additive.
[0056] The organic solvent may be an organic solvent known in the art that can be used in an electrolyte. In some embodiments, the organic solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate, and ethyl propionate.
[0057] The electrolyte salt may be an electrolyte salt known in the art that can be used in an electrolyte. In some embodiments, the electrolyte salt is a lithium salt, and the lithium salt includes at least one of an organic lithium salt or an inorganic lithium salt. In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), bistrifluoromethanesulfonyl imide lithium LiN(CF3SO2)2(LiTFSI), bis(fluorosulfonyl)imide lithium Li(N(SO2F)2)(LiFSI), lithium bis(oxalate borate) LiB(C2O4)2(LiBOB) and lithium difluorooxalate borate LiBF2(C2O4)(LiDFOB). In some embodiments, the lithium salt includes lithium hexafluorophosphate (LiPF6). In some embodiments, the molar concentration of lithium in the lithium salt is about 0.5 mol / L to about 3 mol / L, about 0.5 mol / L to about 2 mol / L, or about 0.8 mol / L to about 1.5 mol / L, based on the volume of the electrolyte.
[0058] The additive may be any additive known in the art that can be used in an electrolyte.
[0059] In some embodiments, the positive electrode sheet is placed in an electrolyte with a volume ratio of ethylene carbonate to dimethyl carbonate of 3:7 and a LiPF6 concentration of 1M, wherein the volume ratio of the mass of the positive electrode active material layer contained in the positive electrode sheet to the electrolyte is 1g / 100mL, and after immersion at 80°C for 1 day, the mass percentage z of the Mn element and the Li element contained in the electrolyte is ≤0.5%, indicating that since HF in the electrolyte is complexed by the phosphorus element, the Mn element is less dissolved in the electrolyte, and therefore the electrochemical device has higher high temperature stability.
[0060] Isolation film
[0061] The separator is a separator known in the art and can be used in electrochemical devices. The separator is disposed between the positive electrode sheet and the negative electrode sheet to prevent short circuit.
[0062] The present application has no particular limitation on the material and shape of the isolation membrane. In some embodiments, the isolation membrane includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0063] In some embodiments, the isolation film includes a substrate layer and a surface treatment layer, wherein the surface treatment layer is disposed on at least one surface of the substrate layer.
[0064] In some embodiments, the substrate layer is a nonwoven fabric, film or composite film with a porous structure. In some embodiments, the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. In some embodiments, the substrate layer is selected from any one of polypropylene porous film, polyethylene porous film, polypropylene nonwoven fabric, polyethylene nonwoven fabric or polypropylene-polyethylene-polypropylene porous composite film.
[0065] In some embodiments, the surface treatment layer is a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. In some embodiments, the inorganic layer includes inorganic particles and a binder, and the inorganic particles are selected from one or more combinations of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate, and the binder is selected from one or more combinations of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylic acid salt, polyvinyl pyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene. In some embodiments, the polymer layer includes a polymer, and the material of the polymer is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).
[0066] Outer packaging shell
[0067] In some embodiments, the electrochemical device further comprises an outer packaging shell. The outer packaging shell is a shell known in the art that can be used in electrochemical devices and is stable to the electrolyte used, such as but not limited to a metal outer packaging shell.
[0068] [Electronic devices]
[0069] The third aspect of the embodiment of the present application provides an electronic device. The electronic device of the present application is any electronic device, such as but not limited to a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini CD, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor. It is noted that the electrochemical device of the present application is applicable to energy storage power stations, sea transport vehicles, and air transport vehicles in addition to the electronic devices listed above. Air transport vehicles include air transport vehicles within the atmosphere and air transport vehicles outside the atmosphere.
[0070] In some embodiments, the electronic device comprises the electrochemical device of the second aspect of the present application.
[0071] The present application is further described below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present application and are not used to limit the scope of the present application.
[0072] In the following examples and comparative examples, the reagents, materials and instruments used can be obtained commercially or synthetically unless otherwise specified.
[0073] Example 1
[0074] (1) Preparation of electrolyte
[0075] In a dry argon environment, organic solvents propylene carbonate (PC), ethylene carbonate (EC), and diethyl carbonate (DEC) are evenly mixed in a weight ratio of 1:1:1, and fully dried lithium salt LiPF6 is added to dissolve in the above organic solvents. After sufficient mixing, an electrolyte with a lithium salt concentration of 1.15 mol / L is obtained.
[0076] (2) Preparation of positive electrode
[0077] The positive electrode active material LiMn2O4 (average particle size D1 is 10μm), the phosphorus-containing compound Al(PO3)3 (average particle size D2 is 5μm), the conductive agent conductive carbon black (Super P), and the binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 97.5:0.5:1:1, and then an appropriate amount of N-methylpyrrolidone (abbreviated as NMP) is added as a solvent. The mixture is stirred and mixed thoroughly to prepare a positive electrode slurry with a solid content of 75% and a viscosity of 5000mPas.
[0078] Then the positive electrode slurry was evenly coated on the aluminum foil, dried at 80°C and then rolled. The thickness of the positive electrode active material layer on one side was 40 μm. The above steps were repeated on the other surface of the positive electrode sheet to obtain a double-sided coated positive electrode sheet.
[0079] (3) Preparation of isolation membrane
[0080] A polyethylene (PE) porous polymer film is used as the isolation membrane.
[0081] (4) Preparation of negative electrode
[0082] The negative electrode active material artificial graphite, the binder styrene-butadiene rubber and the thickener sodium carboxymethyl cellulose (abbreviated as CMC) are fully stirred and mixed in a proper amount of deionized water solvent at a weight ratio of 96:2:2 to form a uniform negative electrode slurry; the negative electrode slurry is coated on a 12 μm thick copper foil, dried, cold pressed, and then cut into pieces and welded to the pole ears to obtain a negative electrode sheet.
[0083] (5) Preparation of lithium-ion batteries
[0084] The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer package, leaving a liquid injection port, and the above-prepared electrolyte is poured from the liquid injection port. After vacuum packaging, standing, formation, shaping and other processes, the preparation of the lithium-ion battery is completed.
[0085] Example 2
[0086] The difference from Example 1 is the preparation of the positive electrode sheet. The weight ratio of the positive electrode active material LiMn2O4, the phosphorus compound Al(PO3)3, the conductive agent conductive carbon black (Super P), and the binder polyvinylidene fluoride (PVDF) is 97:1:1:1. After the positive electrode slurry is evenly coated on the aluminum foil, it is quickly dried at 120°C and then rolled.
[0087] Example 3
[0088] The difference from Example 1 is the preparation of the positive electrode sheet. The weight ratio of the positive electrode active material LiMn2O4, the phosphorus-containing compound Al(PO3)3, the conductive agent conductive carbon black (Super P), and the binder polyvinylidene fluoride (PVDF) is 97:1:1:1.
[0089] Example 4
[0090] The difference from Example 3 is the preparation of the positive electrode sheet. A layered coating method is adopted, firstly coating the positive electrode slurry with a relatively low phosphorus compound ratio on the aluminum foil, drying it, then coating the positive electrode slurry with a relatively high phosphorus compound ratio, and rolling it after drying.
[0091] Example 5
[0092] The difference from Example 3 is the preparation of the positive electrode sheet. A layered coating method is adopted, firstly coating the positive electrode slurry with a higher phosphorus compound ratio on the aluminum foil, drying it, then coating the positive electrode slurry with a lower phosphorus compound ratio, drying it and rolling it.
[0093] Example 6
[0094] The difference from Example 1 is the preparation of the positive electrode sheet. The weight ratio of the positive electrode active material LiMn2O4, the phosphorus compound Al(PO3)3, the conductive agent conductive carbon black (Super P), and the binder polyvinylidene fluoride (PVDF) is 96.5:1.5:1:1. After the positive electrode slurry is evenly coated on the aluminum foil, it is dried at 100°C and then rolled.
[0095] Example 7
[0096] The difference from Example 1 is the preparation of the positive electrode sheet. The weight ratio of the positive electrode active material LiMn2O4, the phosphorus compound Al(PO3)3, the conductive agent conductive carbon black (Super P), and the binder polyvinylidene fluoride (PVDF) is 95:3:1:1. After the positive electrode slurry is evenly coated on the aluminum foil, it is dried at 100°C and then rolled.
[0097] Example 8
[0098] The difference from Example 1 is the preparation of the positive electrode sheet. The weight ratio of the positive electrode active material LiMn2O4 (average particle size D1 is 20 μm), the phosphorus-containing compound is LiPO3 (average particle size D2 is 5 μm), the conductive agent conductive carbon black (Super P), and the binder polyvinylidene fluoride (PVDF) is 97:1:1:1.
[0099] Example 9
[0100] The difference from Example 8 is the preparation of the positive electrode sheet. The phosphorus-containing compound is Ce(PO3)3 (average particle size D2 is 5 μm).
[0101] Example 10
[0102] The difference from Example 8 is the preparation of the positive electrode sheet. The positive electrode active material is LiMn2O4 (average particle size D1 is 25 μm) and the phosphorus-containing compound is NaPO3 (average particle size D2 is 5 μm).
[0103] Embodiment 11
[0104] The difference from Example 1 is the preparation of the positive electrode sheet. The positive electrode active materials LiMn2O4 and LiNi 0.5 Co 0.2 Mn 0.3O2 (average particle size D1 is 10 μm), phosphorus-containing compound Al(PO3)3 (average particle size D2 is 5 μm), conductive agent conductive carbon black (SuperP), and binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 87.3:7.8:1:1:1.
[0105] Example 12
[0106] The difference from Example 1 is the preparation of the positive electrode sheet. Positive electrode active material LiNi 0.5 Co 0.2 Mn 0.3 The weight ratio of O2, phosphorus-containing compound Al(PO3)3, conductive agent conductive carbon black (Super P), and binder polyvinylidene fluoride (PVDF) is 97:1:1:1.
[0107] Embodiment 13
[0108] The difference from Example 2 is the preparation of the positive electrode sheet. Phosphorus-containing compound Al(PO3)3 (average particle size D2 is 0.1 μm).
[0109] Embodiment 14
[0110] The difference from Example 2 is the preparation of the positive electrode sheet. Phosphorus-containing compound Al(PO3)3 (average particle size D2 is 0.2 μm).
[0111] Embodiment 15
[0112] The difference from Example 2 is the preparation of the positive electrode sheet. Phosphorus-containing compound Al(PO3)3 (average particle size D2 is 0.5 μm).
[0113] Example 16
[0114] The difference from Example 2 is the preparation of the positive electrode sheet. The positive electrode active material is LiMn2O4 coated with phosphorus-containing compound Al(PO3)3, and the coating thickness is 20nm.
[0115] Comparative Example 1
[0116] The difference from Example 1 is the preparation of the positive electrode sheet: the positive electrode active material LiMn2O4 (average particle size D1 is 10 μm), the conductive agent conductive carbon black (Super P), and the binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 98:1:1.
[0117] Comparative Example 2
[0118] The difference from Example 1 is the preparation of the positive electrode sheet. The weight ratio of the positive electrode active material LiMn2O4 (average particle size D1 is 10 μm), the phosphorus-containing compound Al(PO3)3 (average particle size D2 is 0.5 μm), the conductive agent conductive carbon black (Super P), and the binder polyvinylidene fluoride (PVDF) is 94:4:1:1.
[0119] Comparative Example 3
[0120] The difference from Example 1 is the preparation of the positive electrode sheet. The weight ratio of the positive electrode active material LiMn2O4 (average particle size D1 is 10 μm), the phosphorus-containing compound Al(PO3)3 (average particle size D2 is 5 μm), the conductive agent conductive carbon black (Super P), and the binder polyvinylidene fluoride (PVDF) is 94:4:1:1.
[0121] Comparative Example 4
[0122] The difference from Example 1 is the preparation of the positive electrode sheet. The weight ratio of the positive electrode active material LiMn2O4 (average particle size D1 is 10 μm), the phosphorus-containing compound Al(PO3)3 (average particle size D2 is 0.1 μm), the conductive agent conductive carbon black (Super P), and the binder polyvinylidene fluoride (PVDF) is 97:1:1:1.
[0123] Comparative Example 5
[0124] The difference from Example 1 is the preparation of the positive electrode sheet. The positive electrode active materials LiMn2O4 and LiNi 0.5 Co 0.2 Mn 0.3 O2 (average particle size D1 is 10 μm), conductive agent conductive carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 88.2:9.8:1:1.
[0125] Lithium-ion battery testing methods
[0126] Element molar ratio test: The formed lithium-ion battery was disassembled to obtain the positive electrode sheet. (1) The distribution of Mn and P elements on the surface of the positive electrode active material layer was tested by SEM-EDX test method. An area of 200 μm × 200 μm was selected from the SEM-EDX image to test the ratio of the number of Mn atoms to the number of P atoms in the entire area. (2) The distribution of P elements on the surface of the positive electrode active material layer and at a depth of 10 μm from the surface was tested by SEM-EDX test method. First, an area of 200 μm × 200 μm was selected from the SEM-EDX image of the surface of the positive electrode active material layer to test the molar ratio of phosphorus to manganese in the entire area. oThen, an area of 200 μm×200 μm was selected from the SEM-EDX image at a depth of 10 μm from the surface of the positive electrode active material layer, and the molar ratio of phosphorus to manganese in the entire area was tested. i ; and then get P o / P i .
[0127] XRD test: The dried positive electrode sheet was kept flat on the sample stage of an XRD test instrument (model Bruker, D8), and an XRD spectrum was obtained using a scanning rate of 2° / min and a scanning angle range of 10° to 90°.
[0128] Average particle size test: Taking the average particle size D2 test of phosphorus-containing compounds as an example, the material powder is photographed and observed by a SEM scanning electron microscope. Then, using image analysis software, 10 phosphorus-containing compound particles are randomly selected from the SEM photos to calculate the area of each of these phosphorus-containing compound particles. Then, assuming that the material particles are spherical, the particle size R (diameter) of each is calculated by the following formula: R = 2 × (S / π) 1 / 2 ; Wherein, S is the area of the phosphorus-containing compound particles; 10 SEM images are processed to determine the particle size R of the phosphorus-containing compound particles, and the particle sizes of the obtained 100 (10×10) phosphorus-containing compound particles are arithmetic averaged to obtain the average particle size D2 of the phosphorus-containing compound particles.
[0129] Raman spectroscopy test: After the lithium-ion battery was discharged to 25% SOC, it was stored at 80°C for 1 day. After disassembly, the positive electrode was washed with dimethyl carbonate solvent and dried at 85°C for 12 hours. Then, it was placed on the sample stage of the Raman test instrument. The peak position was corrected using a silicon wafer. The points on the positive electrode were randomly focused at a focal length of 10+ at 258-846cm. -1 There are two peaks in the wavelength range, and the ratio of the strongest peak to the second strongest peak is taken; 10 points are randomly focused and the average value is recorded as the Raman peak intensity ratio.
[0130] Power-off test: After the positive electrode sheet is dried, one side of the positive electrode active material layer is cleaned with N-methylpyrrolidone (NMP), and vacuum-baked at 85°C for 2h. The small disc required for the positive electrode to punch out the 2025 button battery is taken out, and a button battery is assembled according to the nickel foam, lithium sheet, isolation membrane, and positive electrode disc. 50 microliters of electrolyte is injected. The composition of the electrolyte is EC:PC:DEC=1:1:1, and the concentration of LiPF6 in the electrolyte is 1.15 mol / L.
[0131] The assembled button cell was charged and discharged at a cut-off voltage of about 2.7 to about 4.3 V at 25° C. and a current of 0.2 C to test its gram capacity, where gram capacity = discharge capacity / mass of positive electrode active material.
[0132] The assembled button cell was charged at 45°C at a constant current of 0.5C and then discharged at a constant current of 0.5C. After 50 cycles, the ratio of the amount discharged at the 50th discharge to the initial discharge capacity was calculated.
[0133] Mn / Li content test in electrolyte : The positive electrode sheet was placed in an electrolyte with a volume ratio of ethylene carbonate to dimethyl carbonate of 3:7 and a LiPF6 concentration of 1M. The volume ratio of the mass of the positive electrode active material layer to the electrolyte was 1g / 100mL. After soaking at 80°C for 1 day, the electrolyte was filtered through a 450nm filter head, and the Mn content of the filtrate was measured by a plasma photoelectric direct reading spectrometer (ICP).
[0134] High temperature storage test: The lithium-ion battery was discharged to 30% SOC, and the 100% SOC was recorded as the initial capacity; it was stored in a 60°C oven for 7 days, and then charged and discharged 3 times with a current of 0.2C, and the capacity of the lithium-ion battery at this time was measured and recorded as the recovery capacity after storage. Recovery capacity retention rate (%) = recovery capacity after storage / initial capacity.
[0135] High temperature cycle test: After the lithium-ion battery is formed, it is charged at a constant current of 0.5C and then discharged at a constant current of 1C at 45°C. After 500 cycles, the ratio of the amount of electricity discharged at the 500th discharge to the initial discharge capacity is calculated.
[0136]
[0137] From the data analysis of Table 1, it can be obtained that when the molar ratio of manganese and phosphorus on the surface of the positive electrode active material layer meets the range of 70:1 to 450:1, the interfacial stability of the manganese-containing positive electrode sheet in the electrolyte can be improved, and the high-temperature storage and high-temperature cycle performance of the lithium-ion battery can be significantly improved. From Comparative Examples 2-3, it can be seen that when the molar ratio of manganese and phosphorus on the surface of the positive electrode active material layer is less than 70:1, due to the excessive surface phosphorus compounds, the surface impedance increases and the cycle performance decreases. From Comparative Example 4, it can be seen that when the particle size D2 of the phosphorus-containing compound is smaller than the particle size D1 of the active material, if the drying rate is slow, the phosphorus-containing compound is easy to fill in the gaps between the active materials, thereby enriching in the lower layer of the active material layer, resulting in the molar ratio of manganese and phosphorus on the surface cannot meet the requirements, and the high-temperature storage and cycle cannot be improved well.
[0138] From the data of Examples 2 to 5, it can be obtained that when the total amount of phosphorus in the positive electrode active material layer is the same, the distribution amount of phosphorus on the surface of the positive electrode active material layer and near the surface of the positive electrode active material layer affects the performance of the lithium-ion battery. When it is ensured that there is a considerable amount of phosphorus on the surface of the positive electrode active material layer and inside the positive electrode active material layer near the surface, the high temperature storage and high temperature cycle performance of the lithium-ion battery can be better improved. Example 4 shows that when Po / Pi is 2, due to the relatively low content of internal phosphorus-containing compounds near the surface of the positive electrode active material layer, it cannot be well protected, and thus, its high temperature performance is reduced. While Example 5 shows that when Po / Pi is 0.5, due to the relatively high content of internal phosphorus-containing compounds near the surface of the positive electrode active material layer, the impedance of the surface layer of the positive electrode active material layer increases, and thus, its cycle performance is reduced.
[0139] It can be seen from the data of Examples 2 and 13-15 that when the average particle size D1 of the positive electrode active material and the average particle size D2 of the phosphorus-containing compound satisfy 0.33≤D1 / D2≤100, by controlling the drying rate, the phosphorus-containing compound particles can be evenly distributed in the positive electrode active material layer, and a considerable amount of phosphorus-containing compounds can be ensured on the surface of the positive electrode active material layer and inside the positive electrode active material layer near the surface, which can better improve the high temperature storage and high temperature cycle performance of the lithium-ion battery.
[0140] It can be seen from the data of Example 16 that when the phosphorus-containing compound is coated on the surface of the positive electrode active material, the high-temperature storage and high-temperature cycle performance of the lithium-ion battery can also be greatly improved.
Claims
1. A positive electrode sheet, comprising a positive electrode active material layer, wherein the element content on the surface of the positive electrode active material layer satisfies: a molar ratio of manganese element to phosphorus element is in a range of 70:1 to 450:1; in, The positive electrode active material layer includes a positive electrode active material and a phosphorus-containing compound, and satisfies at least one of the following conditions: i) the average particle size of the positive electrode active material is D1, the average particle size of the phosphorus-containing compound is D2, and 0.33≤D1 / D2≤100; ii) The surface of the positive electrode active material has the phosphorus-containing compound, and the thickness h of the phosphorus-containing compound is 10 nm to 30 nm.
2. The positive electrode sheet according to claim 1, wherein: The thickness of the positive electrode active material layer is H, the molar ratio of phosphorus to manganese on the surface of the positive electrode active material layer is Po; the molar ratio of phosphorus to manganese in the positive electrode active material layer at a depth of H / 4 to H / 3 from the surface of the positive electrode active material layer is P i , P o / P i 0.5 to 2.
3. The positive electrode sheet according to claim 2, wherein: The positive electrode sheet satisfies at least one of the following conditions: 1) The element content on the surface of the positive electrode active material layer satisfies: the molar ratio of manganese element to phosphorus element is in the range of 70:1 to 200:1; 2) P o / P i 1.0 to 1.
38.
4. The positive electrode sheet according to claim 2, wherein: In the XRD spectrum of the surface of the positive electrode active material layer, I A Indicates the peak intensity of the characteristic peak in the range of 20° to 21°, I B Indicates the peak intensity of the characteristic peak in the range of 18° to 18.6°, 0.12≤I A / I B ≤0.
2. The positive electrode sheet according to claim 1 , wherein D1 is 2 μm to 30 μm, and D2 is 0.1 μm to 30 μm.
6. The positive electrode sheet according to claim 1, wherein the phosphorus-containing compound comprises A x PO y , wherein A includes at least one of Li, Na, K, Mg, Ca, Y, Sr, Ba, Zn, Al or Si, 1≤x≤4, 3≤y≤4.
7. The positive electrode sheet according to claim 1, wherein: The positive electrode active material includes at least one of compound a) or compound b): Compound a) Li x1 Mn 2-y1 Z y1 O4, wherein Z includes at least one of Mg, Al, B, Cr, Ni, Co, Zn, Cu, Zr, Ti or V, 0.8≤x1≤1.2, 0≤y1≤0.1; Compound b) Li x2 Ni y2 Co z Mn k M q O b-a T a , wherein M comprises at least one of B, Mg, Al, Si, P, S, Ti, Cr, Fe, Co, Ni, Cu, Zn, Ga, Y, Zr, Mo, Ag, W, In, Sn, Pb, Sb or Ce; T is a halogen, and x2, y2, z, k, q, a and b respectively satisfy: 0.2 ≤ x2 ≤ 1.2, 0 ≤ y2 ≤ 1, 0 ≤ z ≤ 1, 0 < k ≤ 1, 0 ≤ q ≤ 1, 1 < b ≤ 2 and 0 ≤ a ≤ 1.
8. An electrochemical device comprising the positive electrode sheet according to any one of claims 1 to 7.
9. An electronic device comprising the electrochemical device according to claim 8.